Pemanfaatan taman bacaan masyarakat sebagai pusat pembelajaran oleh masyarakat di Nagari Kandang Baru kabupaten Sijunjung - Yogi Prasetia (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2022)
Outdoor Education is education that has programs in order to develop the potential that exists in society. The reading garden in Nagari Kajbaru has been put to good use by the community, the reason being the large collection of books in the Community Reading Center (TBM), the existence of complete supporting facilities, thus the aims of this research are (1) to describe the use of TBM as a learning center by school-age children (2) describe the use of TBM as a learning center by the RT (3) describe the use of TBM as a learning center by farmer groups. This research is a quantitative descriptive study with a population of 51 people and 25 people as a sample. The data collection technique in this study was a questionnaire with percentage data analysis. The results of the study show that the description of TBM utilization includes (1) TBM has been properly utilized by school children as a learning center (2) TBM has been utilized properly by RT mothers as a learning center (3) TBM has been utilized properly by members of farmer groups as learning center.